UPAYA MENINGKATKAN MINAT BELAJAR BAHASA INGGRIS SISWA SEKOLAH DASAR (SD) NEGERI 13 PADANG MENGGUNAKAN METODE TOTAL PHYSICAL RESPONSE - Dwi Megista Putri; Rasmita Rasmita (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2019)
Generallyelementary school students tend to like learning activities with different actions and movements and like the use of visual media. Another problem that is often found in elementary school students is having a very short attention span (short attention span), so they are usually easily bored with learning activities after 7-10 minutes. The tendency of using conventional and monotonous methods given by the school to children, apparently still does not motivate students to study English regularly. Therefore, it is necessary to have innovative and creative actions to minimize the anxiety felt by the school, as well as knowing the talents and learning interests of elementary school students in the English language needs which can be applied in daily activities.